Trading The China Market With American Depository Receipts : How to Play Greater China with a Winning Edge. - Voon, Alan (Wiley, 2012)
Discover the secrets of trading the Chinese markets with American Depository ReceiptsIntroducing a new way to make virtually risk-free profits, Trading the China Market with American Depository Receipts teaches readers how to successfully trade U.S. listed American Depository Receipts (ADRs) of Chinese stocks ... by using information that comes to light outside of Asian trading hours, but while the U.S. markets are still open. Filled with successful strategies for profitable trading made possible by interpreting business news to buy or short China ADRs before the information impacts those ma.